Pengaruh pendidikan kesehatan kombinasi metode simulasi dan media audiovisual terhadap pengetahuan dan sikap ibu terkait tatalaksana diare di rumah pada balita - Aprilia Choirun Nisa; Akhmadi Akhmadi; Mohammad Juffrie (Berita Kedokteran Masyarakat (BKM), 2016)
PurposeThis research aimed to determine the effect of health education related to the management of diarrhea at home in toddler. MethodsThis research was a quasi-experimental study using a pre and post test approach with control group. The sample population was all mothers who attended  Toddler Posyandu in Tiripan village and Ngepeh village, Nganjuk. Sampling technique used simple random sampling totalling 42 mothers in the intervention group and 49 mothers in the control group. Each group was given health education using audio-visual media while the intervention group was given a simulation after watching video. Simulation content included how to create, mix, and giving oralit, sign of dehydration in toddler, and also how to create, dissolve, and giving zinc tablet or syrup. The measurement instrument of mothers knowledge and attitude was made by the researcher  modified from Kapti which had been tested for validity and reliability. Post tests performed 1 week after the health education was given. ResultsIn both groups knowledge and attitude increased significantly after intervention with p=0.001. Changes of mothers knowledge and attitude in control and intervention were p=0.062 and p= 0.658, respectively. This result showed no significant difference in scores of knowledge and attitude of mothers in both groups. ConclusionThere were no significant differences in health education between using combination of simulation method and audiovisual media with increased knowledge and attitude in mothers.